FarGen: Bioresource From the Faroe Genome Project. (28th June 2021) - Gregersen, Noomi Oddmarsdóttir; Apol, Katrin Didriksen; Weihe, Pál; Steig, Bjarni Á.; Andorsdóttir, Guðrið
The Faroe Genome Project (FarGen) explores the genetic variation within the isolated population of the Faroe Islands. FarGen is an open bioresource comprising 3% of the entire Faroese population, available for further investigation of both rare and common diseases. The 1, 541 volunteers include representatives from all sub-regions of the islands, and health- and socio-demographic data is collected by questionnaire, Multi-Generation Registry, Diagnostic-Registry, and National Registry. The FarGen-infrastructure is already open to research teams, and is being used in research of various complex disorders. Future aim is to reach 5000 samples i.e. 10% of the entire Faroese population.